Proximal Aortic Dilatation and Pulmonary Valve Replacement in Patients with Repaired Tetralogy of Fallot: Is There a Relationship? A Cardiac Magnetic Resonance Imaging Study - Ahmed Farghal A. Mohammed (MDPI AG, 2021)
Aortopathy is a known complication whose incidence is growing within the population of tetralogy of Fallot (TOF) patients. Its pathology and relationship with other comorbidities remain unclear. This study was designed to determine the prevalence and predictors of proximal aortic dilatation after TOF repair. We retrospectively investigated all patients who underwent follow-up cardiac magnetic resonance imaging (CMR; at least 4 years after TOF repair) between March 2004 and December 2019. The dimensions at the ascending aorta (AAo) and sinus of Valsalva (SoV) levels were measured. Aortic dilatation was defined as an internal aortic diameter that was >2 standard deviation of the previously published normal values. We included 77 patients (mean age 28.9 ± 10.5 years, 41.5% female, mean follow-up of 24.5 ± 8.1 years). AAo and SoV were dilated in 19 (24.6%) and 43 (55.8%) patients, respectively. Patients with dilated AAo and SoV were older during the corrective surgery (p < 0.001 and p = 0.004, respectively) and during CMR (p = 0.002 and 0.024, respectively) than patients without AAo and SoV dilatation. Patients of the dilated AAo group were more likely to have prior palliative shunt (p = 0.008), longer shunt duration (p = 0.005), and a higher degree of aortic valve regurgitation (AR) fraction (p < 0.001) and to undergo pulmonary (PVR) and/or aortic valve replacement (p < 0.001 and p = 0.013, respectively). PVR (p = 0.048, odds ratio = 6.413, and 95% CI = 1.013–40.619) and higher AR fraction (p = 0.031, odds ratio = 1.194, and 95% CI = 1.017–1.403) were independent predictors for AAo dilatation. Aortopathy is a common progressive complication that may require reintervention and lifelong follow-up. Our study shows that proximal aortic dilatation may be attributed to factors that increase the volume overload across the proximal aorta, including late corrective surgery and palliative shunt. We also found that PVR and higher AR fraction are independent predictors of AAo dilatation.